High-quality copper-nickel composite interface cone and preparation method thereof
By directly electrodepositing the copper or copper alloy matrix and nickel layer on the interface cone, and performing secondary electrodeposition and shot peening strengthening of the cone port, the corrosion problems of the interface cone in acidic and alkaline media and the poor bonding force of traditional materials are solved, and a high-quality, long-life and corrosion-resistant interface cone preparation is achieved.
Patent Information
- Application Number
- CN202411979889.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing interface cones have corrosion problems in acidic and alkaline media, and the heat dissipation materials prepared by traditional high-temperature smelting and mechanical alloying methods have poor binding force, making it difficult to use in a harsh environment of high-temperature corrosion.
Copper or copper alloy matrix is prepared by direct electrodeposition on conical structural plates, nickel is directly electrodeposition on the substrate, nickel or platinum coating is secondary electrodeposition on the cone port and shot peening is strengthened to prepare a uniform and dense high-quality copper-nickel composite interface cone.
It realizes high-quality preparation of interface cones, can work continuously for ≥1000h in a water-cooled working environment of 4000-6000K, have a lifespan of ≥24 months, and can withstand strong acid and alkali environmental corrosion of pH = 1-3 and pH = 8-9.
Smart Images

Figure CN119864273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inductively coupled plasma mass spectrometry (ICP-MS), and in particular to a high-quality copper-nickel composite interface cone and a preparation method thereof. Background Art
[0002] The interface cone is a key component of the plasma mass spectrometer, which is divided into a sampling cone and a skimmer cone. It plays an important role in high-temperature plasma extraction, ion transmission and focusing, vacuum differential, etc. Its characteristics directly affect the instrument's sensitivity, noise, life, acid and alkali resistance, etc. The interface cone parts work in a harsh environment, at high temperatures (about 6000K) and strong acid and alkali environments, so the interface cone parts are required to meet the requirements of high temperature resistance, corrosion resistance and good thermal conductivity.
[0003] In the prior art, Chinese patent CN201549467U discloses a glow discharge ion source mass spectrometer interface device, in which the interface cone and the intercepting cone are made of pure nickel material or stainless steel material, are easy to install, durable, and have good use effect, but do not mention indicators such as the high temperature resistance and corrosion resistance of the interface cone parts; Chinese patent CN212461599U discloses a novel inductively coupled plasma mass spectrometer sampling cone, in which a protective heat dissipation device is installed on the cone to achieve heat dissipation and heat resistance, and heat dissipation fins are arranged around the sides of the heat dissipation column, all of which are made of copper, but the sampling cone structure design is relatively complex and the cost is relatively high; Chinese patent CN117758330A discloses an anti-corrosion treatment method for an ICP-MS interface nickel cone, in which a hard chromium layer and a titanium alloy layer are successively plated on the surface of the nickel cone, but the above technology still has a certain degree of corrosion in actual application.
[0004] In summary, in the prior art, the interface cone device still suffers from a certain degree of corrosion in acidic and alkaline media, and the above-mentioned corrosion will be aggravated in a high temperature and oxygen environment; in addition, in terms of heat resistance, a heat dissipation device is installed on the cone, which has a complex structure, and the heat dissipation material is prepared by traditional high-temperature smelting and mechanical alloying methods. For example, Chinese patent CN111128929A uses traditional calendering and machining processes to prepare heat dissipation materials. The material bonding force is poor, and it is difficult to use it for a long time in a harsh working environment of high temperature corrosion. The preparation process of heterogeneous material composite molding is complex and the production cost is high. Summary of the invention
[0005] In order to solve the problem of poor bonding strength and short life of heterogeneous materials of interface cones, the present invention proposes a high-quality copper-nickel composite interface cone and a preparation method thereof, wherein a copper or copper alloy substrate is prepared by direct electrodeposition on a cone-shaped structure seed plate, nickel is directly electrodeposited on the substrate, a nickel or platinum coating is secondary electrodeposited on the cone mouth, and shot peening is performed to prepare a uniform, dense, high-quality copper-nickel interface cone for ICP-MS. The specific preparation method is as follows:
[0006] A method for preparing a high-quality copper-nickel composite interface cone comprises the following steps:
[0007] Step 1: Processing titanium or stainless steel into an electrodeposited seed plate, wherein the seed plate structure comprises a circular base and a conical structure on the base, wherein the bottom surface of the conical structure is connected to the inner circle of the circular base, and a conical opening is provided at the end of the conical structure;
[0008] Step 2: Insulating the inner side of the seed plate, then placing the seed plate in a copper-containing solution with a copper content of 80-150 g / L for single-sided electrodeposition on the outer side, with an electrodeposition thickness of 1-3 mm, peeling off to obtain a copper or copper alloy substrate, and machining the copper or copper alloy substrate until the thickness of the copper or copper alloy substrate at the cone mouth of the cone structure is 0.1-0.3 mm;
[0009] Step 3: placing the copper or copper alloy substrate in a nickel-containing solution with a nickel content of 80-100 g / L, performing pulse electrodeposition with an electrodeposition thickness of 0.3-0.5 mm, and preparing a copper-nickel composite interface cone;
[0010] Step 4: placing the end of the conical structure of the copper-nickel composite interface cone in a nickel-containing or platinum-containing solution for electrodeposition, the electrodeposition thickness of which is 0.5-0.8 mm, and then strengthening the end of the conical structure to obtain a high-quality copper-nickel composite interface cone.
[0011] Furthermore, the copper-containing solution in step 2 is one or more of a copper sulfate solution, a copper chloride solution, a beryllium nickel copper solution, and a tungsten copper solution.
[0012] Furthermore, the process parameters of the electrodeposition process in step 2 are: temperature 30-50°C, current density 100-200A / m 2 , pH value is 1-3, and the electrodeposition time is 24-48h.
[0013] Furthermore, the nickel-containing solution in step 3 is one or more of nickel chloride or nickel sulfate. Furthermore, the process parameters of the pulse electrodeposition process in step 3 are: pulse duty ratio (1:3)-(4:1), electrodeposition temperature 20-30°C, current density 30-40A / m 2 , pH value 3.5-5.5, electrodeposition time 16-24h.
[0014] Furthermore, in step 4, the portion from the cone mouth to 1 / 3-1 / 2 of the cone structure below the cone mouth of the copper-nickel composite interface cone is placed in a nickel-containing or platinum-containing solution.
[0015] Furthermore, the concentration of nickel or platinum in the nickel-containing or platinum-containing solution in step 4 is 120-150 g / L, and the electrodeposition process parameters are: temperature 30-50° C., current density 40-100 A / m 2 , pH value is 1-3, and the electrodeposition time is 20-30h.
[0016] Furthermore, in step 4, shot peening treatment is performed, the shot peening intensity is 0.5-1.0 MPa, and the coverage rate is 100-200%.
[0017] The high-quality copper-nickel composite interface cone prepared according to the above method comprises a circular ring base and a conical structure on the base, the bottom surface of the conical structure is connected to the inner circle of the circular ring base, the copper-nickel composite interface cone is a copper or copper alloy substrate and a nickel layer from the inside to the outside, and the nickel layer at the end of the conical structure is a nickel or nickel alloy or platinum alloy coating; the copper or copper alloy substrate has a thickness of 1-3mm and a density of 99.80-99.98%; the nickel layer has a purity of ≥99.99%, a density of 99.90-99.98%, a thickness of 0.3-0.5mm, a porosity of ≤1%, a grain size of ≤1μm, a roughness of ≤1μm, and a defect rate of ≤0.5%; the nickel or nickel alloy or platinum alloy coating has a thickness of 0.5-0.8mm and a hardness of ≥120HV.
[0018] Furthermore, the outer diameter of the annular base is 50-80 mm, the taper of the conical structure is 100-150%, and the diameter of the cone opening of the conical structure is 0.7-1.2 mm.
[0019] The beneficial effects of the present invention are as follows: the present invention prepares an interface cone comprising a copper or copper alloy substrate, a nickel layer and a thick treatment strengthening coating on the cone mouth part; the present invention controls the thickness and density of the deposited layer by adjusting parameters such as the electrodeposition current, voltage, temperature, current density and acidity, and can achieve uniform deposition without using a dispersant; under the process conditions of the present invention, the substrate copper density can reach 99.80-99.98%, and the problems of difficult control of the composition and thickness of the smelting preparation of copper or copper alloy, easy introduction of impurities, high energy consumption and high cost can be completely avoided; at the same time, the prepared electrodeposited nickel layer has a purity of ≥99.99%, a density of 99.90-99.98%, a thickness of 0.3-0.5 mm, a porosity of ≤1%, a grain size of ≤1 μm, a roughness of ≤1 μm, a defect rate of ≤0.5%, high heterogeneous metal bonding force and high uniformity; at the same time, the cone mouth is subjected to thick treatment (i.e., secondary electrodeposition of nickel coating or platinum coating) and shot peening strengthening, which can solve the corrosion problem of the existing interface cone in acidic or alkaline media in actual detection. The interface cone preparation method of the present invention solves the problem of the difficulty of combining traditional welding processes of heterogeneous materials, and the process is simple. The prepared interface cone can withstand a 4000-6000K water-cooled working environment, with a continuous working time of ≥1000h and a lifespan of ≥24 months, and can withstand corrosion in strong acid and alkali environments of pH=1-3 and pH=8-9. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0021] Figure 1 A process flow chart of a method for preparing a high-quality copper-nickel composite interface cone of the present invention is shown;
[0022] Figure 2 The structural cross-sectional view of the copper-nickel composite interface cone prepared by the present invention is shown;
[0023] Figure 3 A schematic structural diagram of the copper-nickel composite interface cone prepared by the present invention is shown.
[0024] Among them, 1: electrodeposited copper or copper alloy substrate, 2: electrodeposited nickel layer, 3: nickel or nickel alloy or platinum alloy coating. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] A method for preparing a high-quality copper-nickel composite interface cone comprises the following steps:
[0027] Step 1: Processing titanium or stainless steel into an electrodeposited seed plate, wherein the seed plate structure comprises a circular base and a conical structure on the base, wherein the bottom surface of the conical structure is connected to the inner circle of the circular base, and a conical opening is provided at the end of the conical structure;
[0028] Step 2: Insulate the inner side of the seed plate, then place the seed plate in a copper-containing solution with a copper content of 80-150g / L for single-sided electrodeposition on the outer side, the electrodeposition thickness is 1-3mm, peel off to obtain a copper or copper alloy matrix, and machine the copper or copper alloy matrix to a cone mouth of a cone structure, the thickness of the copper or copper alloy matrix is 0.1-0.3mm; the copper-containing solution is one or more of a copper sulfate solution, a copper chloride solution, a beryllium nickel copper solution, and a tungsten copper solution. The process parameters of the electrodeposition process are: temperature 30-50°C, current density 100-200A / m 2 , pH value is 1-3, and the electrodeposition time is 24-48h.
[0029] Step 3: placing the copper or copper alloy substrate in a nickel-containing solution with a nickel content of 80-100 g / L, performing pulse electrodeposition, and the electrodeposition thickness is 0.3-0.5 mm to prepare a copper-nickel composite interface cone; the nickel-containing solution is one or more of nickel chloride or nickel sulfate, and the process parameters of the pulse electrodeposition process are: pulse duty ratio (1:3)-(4:1), electrodeposition temperature 20-30°C, current density 30-40A / m 2 , pH value 3.5-5.5, electrodeposition time 16-24h.
[0030] Step 4: Place the end of the copper-nickel composite interface cone in a nickel- or platinum-containing solution for electrodeposition of a large thickness, the electrodeposition thickness is 0.5-0.8mm, and then strengthen the end of the cone structure to obtain a high-quality copper-nickel composite interface cone. The large thickness treatment part specifically refers to the 1 / 3-1 / 2 part of the cone structure from the cone mouth to the cone mouth, that is, the nickel or nickel alloy or platinum alloy coating; the nickel or platinum concentration in the nickel- or platinum-containing solution is 120-150g / L, the temperature is 30-50℃, and the current density is 40-100A / m 2 , pH value 1-3, electrodeposition time 20-30h, strengthening treatment is shot peening strengthening treatment, shot peening intensity is 0.5-1.0MPa, coverage rate is 100-200%.
[0031] Example 1
[0032] A method for preparing a high-quality copper-nickel composite interface cone comprises the following steps:
[0033] (1) A titanium plate is processed into a circular base and a conical structure on the base, wherein the outer diameter of the circular base of the seed plate is 50 mm, the taper of the conical structure is 100%, the diameter of the cone opening is 0.7 mm, and the thickness is 1 mm. A titanium seed plate for electrodeposition is prepared.
[0034] (2) After the inner side of the titanium seed plate is insulated, it is placed in a copper sulfate solution containing 80g / L of copper, and the power is turned on. The temperature is controlled at 30°C and the current density is 100A / m 2 , pH value 1, copper substrate thickness after electrodeposition is 1 mm, electrodeposition time is 24 h. The copper substrate is peeled off and machined, and the thickness of the copper or copper alloy substrate at the cone mouth of the cone structure is 0.1 mm.
[0035] (3) The copper substrate was placed in a nickel chloride solution with a nickel content of 90 g / L and pulsed electrodeposited with a pulse duty ratio of 1:3, an electrodeposition temperature of 20 °C, and a current density of 30 A / m 2 , pH value 3.5, electrodeposition time 20h, and the copper-nickel composite interface cone was prepared.
[0036] (4) Place 1 / 2 of the conical structure from the cone mouth to the bottom of the cone mouth of the copper-nickel composite interface cone in a nickel-containing solution for secondary electrodeposition, with a nickel content of 120 g / L, an electrodeposition temperature of 30 °C, and a current density of 40 A / m 2 , pH value 1, electrodeposition time 20h, a thick nickel coating is formed near the cone mouth, the cone mouth coating thickness is 0.5mm, the cone mouth coating is shot peened, the shot peening intensity is 0.5MPa, the coverage rate is 100%, and then the high-quality copper-nickel composite interface cone is obtained after surface treatment.
[0037] The purity of the electro-deposited nickel layer is 99.992%, the density is 99.95%, the thickness is 0.3mm, the porosity of the electro-deposited layer is 0.8%, the grain size is 1μm, the roughness is 1μm, and the defect rate is 0.5%; the cone thickness is 0.9mm and the hardness is 120HV. The copper-nickel composite interface cone can work continuously for 1200h in a 4000K water-cooled working environment, and the interface cone has a life of 24 months. It can withstand corrosion in strong acid and alkali environments of pH=1 and pH=8.
[0038] Example 2
[0039] A method for preparing a high-quality copper-nickel composite interface cone comprises the following steps:
[0040] (1) A stainless steel plate is processed into a circular base and a conical structure on the base, wherein the outer diameter of the circular base of the seed plate is 80 mm, the taper of the conical structure is 120%, the diameter of the cone opening is 1.0 mm, and the thickness is 2 mm. A stainless steel seed plate for electrodeposition is prepared.
[0041] (2) The inner side of the stainless steel plate is covered with insulating material as the cathode and placed in a copper chloride solution containing 150g / L copper. A pulse power supply is connected and the temperature is controlled at 50°C and the current density is 200A / m 2 , pH value 3, electrodeposition time 48h, copper substrate thickness after electrodeposition is 2mm. The copper substrate is peeled off and machined, and the thickness of the copper or copper alloy substrate at the cone mouth of the cone structure is 0.2mm.
[0042] (3) The copper substrate was placed in a nickel sulfate solution with a nickel content of 80 g / L and pulsed electrodeposited with a pulse duty ratio of 4:1, an electrodeposition temperature of 30 °C, and a current density of 40 A / m 2 , pH value 5, electrodeposition time 24h, and the copper-nickel composite interface cone was prepared.
[0043] (4) The cone mouth of the copper-nickel composite interface cone is placed in a platinum-containing solution from 1 / 3 of the cone mouth outer diameter for secondary electrodeposition. The platinum content is 150 g / L, the electrodeposition temperature is 50 °C, and the current density is 100 A / m 2 , pH value 3, a platinum coating is formed near the cone mouth, the electrodeposition time is 30h, the cone mouth coating thickness is 0.5mm, the cone mouth coating is shot peened, the shot peening intensity is 0.7MPa, the coverage rate is 120%, and then the high-quality copper-nickel composite interface cone is obtained after surface treatment.
[0044] The purity of the electrodeposited nickel layer is 99.992%, the density is 99.95%, the thickness of the electrodeposited nickel is 0.5mm, the porosity of the electrodeposited layer is 0.6%, the grain size is 0.7μm, the roughness is 0.8μm, and the defect rate is 0.4%; the cone thickness is 1.2mm, and the hardness is 130HV. The copper-nickel composite interface cone can work continuously for 1000 hours under a 6000K water-cooled working environment, and the interface cone has a life of 30 months. It can withstand corrosion in strong acid and alkali environments of pH=3 and pH=9.
[0045] Example 3
[0046] A method for preparing a high-quality copper-nickel composite interface cone comprises the following steps:
[0047] (1) The titanium plate is processed into a circular base and a conical structure on the base, the outer diameter of the circular base of the seed plate is 70 mm, the taper of the conical structure is 130%, the diameter of the cone opening is 1.2 mm, and the thickness is 1.2 mm. A titanium seed plate for electrodeposition is prepared.
[0048] (2) After the inner side of the titanium seed plate is insulated, it is placed in a beryllium nickel copper solution containing 100 g / L copper. The power is turned on and the temperature is controlled at 40°C and the current density is 150 A / m 2, pH value 2, copper substrate thickness after electrodeposition is 1.5 mm, electrodeposition time is 36 h. The copper substrate is peeled off and machined, and the thickness of the copper or copper alloy substrate at the cone mouth of the cone structure is 0.3 mm.
[0049] (3) The copper substrate was placed in a nickel sulfate solution with a nickel content of 80 g / L and pulsed electrodeposited with a pulse duty ratio of 2:1, an electrodeposition temperature of 25 °C, and a current density of 30 A / m 2 , pH value 4, electrodeposition time 18h, and the copper-nickel composite interface cone was prepared.
[0050] (4) The cone mouth of the copper-nickel composite interface cone is placed in a platinum-containing solution from 1 / 3 of the cone mouth outer diameter for secondary electrodeposition. The platinum content is 120 g / L, the electrodeposition temperature is 40 °C, and the current density is 80 A / m 2 , pH value 2, a platinum coating is formed near the cone mouth, the electrodeposition time is 20 hours, the cone mouth coating thickness is 0.8 mm, the cone mouth coating is shot peened, the shot peening intensity is 0.8 MPa, the coverage rate is 150%, and then the high-quality copper-nickel composite interface cone is obtained after surface treatment.
[0051] The purity of the electrodeposited nickel layer is 99.991%, the density is 99.98%, the thickness of the electrodeposited nickel is 0.4mm, the porosity of the electrodeposited layer is 0.9%, the grain size is 0.6μm, the roughness is 0.8μm, and the defect rate is 0.5%. The cone thickness is 1.5mm and the hardness is 130HV. The interface nickel cone can work continuously for 1000h under a 5000K water-cooled working environment, and the interface cone has a life of 30 months. It can withstand corrosion in strong acid and alkali environments of pH=2 and pH=8.
[0052] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for preparing a high-quality copper-nickel composite interface cone, characterized in that: The following steps are involved: Step 1: Processing titanium or stainless steel into an electrodeposited seed plate, wherein the seed plate structure comprises a circular base and a conical structure on the base, wherein the bottom surface of the conical structure is connected to the inner circle of the circular base, and a conical opening is provided at the end of the conical structure; Step 2: Insulating the inner side of the seed plate, then placing the seed plate in a copper-containing solution with a copper content of 80-150 g / L for single-sided electrodeposition on the outer side, with an electrodeposition thickness of 1-3 mm, peeling off to obtain a copper or copper alloy substrate, and machining the copper or copper alloy substrate until the thickness of the copper or copper alloy substrate at the cone mouth of the cone structure is 0.1-0.3 mm; Step 3: placing the copper or copper alloy substrate in a nickel-containing solution with a nickel content of 80-100 g / L, performing pulse electrodeposition with an electrodeposition thickness of 0.3-0.5 mm, and preparing a copper-nickel composite interface cone; Step 4: placing the end of the conical structure of the copper-nickel composite interface cone in a nickel-containing or platinum-containing solution for electrodeposition, the electrodeposition thickness of which is 0.5-0.8 mm, and then strengthening the end of the conical structure to obtain a high-quality copper-nickel composite interface cone.
2. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: The copper-containing solution in step 2 is one or more of a copper sulfate solution, a copper chloride solution, a beryllium nickel copper solution, and a tungsten copper solution.
3. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: Step 2 The process parameters of the electrodeposition process are: temperature 30-50°C, current density 100-200A / m 2 , pH value is 1-3, and the electrodeposition time is 24-48h.
4. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: The nickel-containing solution in step 3 is one or more of nickel chloride or nickel sulfate.
5. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: The process parameters of the pulse electrodeposition process in step 3 are: pulse duty ratio 1:3-4:1, electrodeposition temperature 20-30°C, current density 30-40A / m 2 , pH value 3.5-5.5, electrodeposition time 16-24h.
6. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: In step 4, the portion from the cone mouth to 1 / 3-1 / 2 of the cone structure below the cone mouth of the copper-nickel composite interface cone is placed in a nickel-containing or platinum-containing solution.
7. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: The concentration of nickel or platinum in the nickel or platinum-containing solution in step 4 is 120-150 g / L, and the electrodeposition process parameters are: temperature 30-50°C, current density 40-100 A / m 2 , pH value is 1-3, and the electrodeposition time is 20-30h.
8. The method for preparing a high-quality copper-nickel composite interface cone according to claim 1, characterized in that: In step 4, shot peening treatment is performed, the shot peening intensity is 0.5-1.0 MPa, and the coverage rate is 100-200%.
9. The high-quality copper-nickel composite interface cone prepared according to the method according to any one of claims 1 to 8, characterized in that: The copper-nickel composite interface cone comprises a circular ring base and a conical structure on the base, the bottom surface of the conical structure is connected to the inner circle of the circular ring base, the copper-nickel composite interface cone is a copper or copper alloy substrate and a nickel layer from the inside to the outside, and the nickel layer at the end of the conical structure is a nickel or nickel alloy or platinum alloy coating; the copper or copper alloy substrate has a thickness of 1-3mm and a density of 99.80-99.98%; the nickel layer has a purity of ≥99.99%, a density of 99.90-99.98%, a thickness of 0.3-0.5mm, a porosity of ≤1%, a grain size of ≤1μm, a roughness of ≤1μm, and a defect rate of ≤0.5%; the nickel or nickel alloy or platinum alloy coating has a thickness of 0.5-0.8mm and a hardness of ≥120HV.
10. The high-quality copper-nickel composite interface cone according to claim 9, characterized in that: The outer diameter of the annular base is 50-80 mm, the taper of the conical structure is 100-150%, and the diameter of the cone opening of the conical structure is 0.7-1.2 mm.
Citation Information
Patent Citations
Heat dissipation material and processing technology thereof
CN111128929A
Anti-corrosion treatment method for ICP-MS interface nickel cone and anti-corrosion nickel cone
CN117758330A
Interface device utilizing glow-discharge ion source mass spectrometry
CN201549467U
Novel inductively coupled plasma mass spectrometer sampling cone
CN212461599U
Integrated molecular beam sampling interface
CN112557488A